Triclosan and bisphenol a affect decidualization of human endometrial stromal cells. (15th February 2016) - Forte, Maurizio; Mita, Luigi; Cobellis, Luigi; Merafina, Verdiana; Specchio, Raffaella; Rossi, Sergio; Mita, Damiano Gustavo; Mosca, Lavinia; Castaldi, Maria Antonietta; De Falco, Maria; Laforgia, Vincenza; Crispi, Stefania
Abstract: In recent years, impaired fertility and endometrium related diseases are increased. Many evidences suggest that environmental pollution might be considered a risk factor for endometrial physiopathology. Among environmental pollutants, endocrine disrupting chemicals (EDCs) act on endocrine system, causing hormonal imbalance which, in turn, leads to female and male reproductive dysfunctions. In this work, we studied the effects of triclosan (TCL) and bisphenol A (BPA), two widespread EDCs, on human endometrial stromal cells (ESCs), derived from endometrial biopsies from woman not affected by endometriosis. Cell proliferation, cell cycle, migration and decidualization mechanisms were investigated. Treatments have been performed with both the EDCs separately or in presence and in absence of progesterone used as decidualization stimulus. Both TCL and BPA did not affect cell proliferation, but they arrested ESCs at G2/M phase of cell cycle enhancing cell migration. TCL and BPA also increased gene expression and protein levels of some decidualization markers, such as insulin growth factor binding protein 1 (IGFBP1) and prolactin (PRL), amplifying the effect of progesterone alone. All together, our data strongly suggest that TCL and BPA might alter human endometrium physiology so affecting fertility and pregnancy outcome. Highlights: Low TCL and BPA concentrations affect human ESCs physiology. Progesterone induced decidualization is enhanced by TCL and BPA. TCL shows more effects compared to BPA on ESCs. TCL and BPA induce ESCs migration. Exposure to EDCs may be a risk factor for fertility.